Resposta :
Resposta:
A.
[tex]+\frac{14}{5} + (-2,5)=\\\\+\frac{14}{5} -2,5=\\\\+\frac{14}{5_{(\times2)}} - \frac{25}{10} =\\\\+\frac{28}{10} -\frac{25}{10} =\\\\\frac{3}{10}[/tex]
B.
[tex]+\frac{6}{10} - (-0,2)=\\\\+\frac{6}{10} + 0,2=\\\\+\frac{6}{10} + \frac{2}{10} =\\\\\frac{8}{10_{(:2)}} =\\\\\frac{4}{5}[/tex]
C.
[tex]+\frac{3}{10} + (-1,2)=\\\\+\frac{3}{10} -1,2=\\\\+\frac{3}{10} - \frac{12}{10} =\\\\-\frac{9}{10}[/tex]
D.
[tex]+\frac{1}{10} - (-0,1)=\\\\+\frac{1}{10} + 0,1=\\\\+\frac{1}{10} + \frac{1}{10} =\\\\\frac{2}{10_{(:2)}}=\frac{1}{5}[/tex]